CO2 Flux from Tropical Land Uses on Andisol in West Java, Indonesia - Hendri, Jon; Sumawinata, Basuki; Baskoro, Dwi Putro Tejo (UNIVERSITY OF LAMPUNG, 2014)
This study measured CO2 flux by segregating effect of root respiration and organic matter decomposition by microbes. The study involved a mineral soil containing high organic matter (Andisols), in the tropic devoted to different land uses i.e. natural forest, tea plantation, and horticultural farm CO2 emission from those land uses were compared to from peatland. Observed CO2 fluxes came out in the following order: bare plot 7.32, tea plantation 10.22, horticultural farm 15.60, and natural forest 15.62 Mg C-CO2 ha-1 yr-1. While, root respiration accounted for substantial proportions: tea plantation 28%, horticultural farm 53%, and natural forest 53%. Soil temperature demonstrated a significant positive correlation with the CO2 flux, except in the natural forest. On the other hand, water-filled pore spaces displayed varying correlation with site CO2 flux: a negative relationship in both bare plot and tea plantation, appreciably positive in the horticultural farm, and weakly related in the natural forest. Soil respiration and C-organic content appeared to be strongly correlated; the rate of soil respiration increased with higher C-organic content. In field, CO2 flux from organic matter decomposition in Andisols, Latosols, and peatland ranged from 5.35-13.22 Mg C-CO2 ha-1 yr-1, with root respiration contributing most of the flux, which was, in turn, influenced by type vegetation, humidity and soil temperature.Keywords: CO2 flux; decomposition; horticultural farm; natural forest; organic matter; tea plantation [How to Cite: Jon H, Suwardi, B Sumawinata and DPT Baskoro. 2014. CO2 Flux from Tropical Land Uses on Andisol in West Java, Indonesia. J Trop Soils 19: 121-130. Doi: 10.5400/jts.2014.19.3.121]